Stripping of Platinum Loaded from Hydrochloric Acid Solutions with APT 6500 and TBP Mixed Extractants - YOKOTA, Harumi; HIRAI, Sota; KARIYA, Rento; KADOWAKI, Takayuki; NIINAE, Masakazu (Resources processing, 2025)
Chloride is one of the effective medium in which platinum group metals (PGMs) can be brought into a solution. Solvent extraction applied to refining process for PGMs offers several advantages over the traditional precipitation methods and distillation. Extraction and separation of Pt(IV) and Pd(II) from hydrochloric acid solutions was possible to extract Pt(IV) and suppress the extraction of Pd(II) using mixed extractants of APT 6500 (bis(2,4,4-trimethylpentyl)phosphinic acid), an acidic extractant and TBP (tri-n-butyl phosphate), a solvation extractant. However, the stripping of Pt(IV) loaded with mixed extractants of APT 6500 and TBP has not been investigated at all. In this study, the stripping of Pt(IV) loaded from hydrochloric acid solutions using mixed extractants of APT 6500 and TBP was investigated. As a result of the study, it was found that acids and ammonium chloride solutions were not effective for stripping of Pt(IV) loaded with mixed extractants of APT 6500 and TBP, but solutions of sodium sulfate, sodium nitrate, sodium perchlorate and sodium acetate were each effective. Also, it was found that the composition of APT 6500 and TBP concentrations, especially the TBP concentration, affected the stripping of Pt(IV).